Diversity, distribution and chemotaxonomy of macro lichens at Mesilau Nature Park, Sabah - Mathavan Vickneswaran (2014)
Mesilau Nature Park is a hotspot for macro lichens but no detail research is done on the distribution and diversity of this organism. Since 1993, there are no further records or research on lichens at Mesilau Nature Park. Hence, this project is started with the objective to survey for macro lichen's distribution and diversity, followed by production of a checklist of macro lichens at Mesilau Nature Park and to compare similar occurring genera at three different sites, Mesilau Nature Park, Mount Alab and Mount Trus Madi. Mesilau Nature Park was divided into four different sampling zones. As Zone 1 is a small patch, it is excluded from the distribution and diversity measures but a small checklist was produced as an outcome. Meanwhile, the sampling area and distance was standardized for the zones 1,2 and 3. This is done to measure their distribution and diversity of macro lichens. At the end of the sampling, in total 143 samples of macro lichens was collected with 21 genera recorded. Three different diversity index, Shannon-wiener diversity index, Simpson's Diversity index and Kruskal-Wallis test, were calculated based on each sampling zones. Zone 3 was recorded to have the highest diversity with total of 16 genera (35 samples) recorded. Meanwhile, Zone 4 records the lowest diversity with only 5 genera (7 samples) recorded. The extant of similar occurring genera of macro lichens at three different sampling sites, Mesilau Nature Park, Mount Alab and Mount Trus Madi, made it possible for comparison between these three sites to be carried out. Three species was choosed for comparison purpose, where two species from the genus Cladonia and one species from the genus Stereocaulon. Chemical profiling using Thin Layer Chromatography (TLC) and High Performance Liquid Chromatography were performed on all nine samples. Outcome of the profiling indicates certain amount of similarly occurring compounds within samples of same species. Abundance of compounds within lichen material may be influenced by different environmental parameters and climatic factor at each sampling sites. Therefore, research on distribution of macro lichens and accumulation of lichen compounds within lichen material will be very beneficial in further understanding macro lichens."